Impulsividade no traumatismo cranioencefálico leve: investigação clínica, neuropsicológica e de biomarcadores séricos inflamatórios, neuronais e de dano vascular - Maíra Glória de Freitas Cardoso (2021)
Cognitive, behavioral, and neuropsychiatric changes are commonly observed in patients with moderate and severe traumatic brain injury (TBI). Growing evidence supports that patients with mild TBI also have these changes. The aim of this work was to investigate cognitive alterations in patients with mild TBI in the acute stage and to investigate cognitive and behavioral alterations and associated biomarkers up to one month after TBI. The result is divided into three studies: 1) article on cognitive assessment in mild TBI up to 24 hours after trauma; 2) systematic review of impulsivity in TBI; and 3) article on the assessment of impulsivity, cognitive and behavioral changes, and blood markers in mild TBI patients within one month after TBI. The common methodology of studies 1 and 3 included patients with mild TBI treated at the neurology emergency room at Hospital João XXIII up to 24 hours after mild TBI. Patients were assessed using cognitive tests and self-report scales. In study 3, inflammatory, neuronal, and vascular markers were also measured in the serum of patients and controls in an exploratory manner. In study 1, patients with mild TBI (n=53) had worse performance in general cognition, episodic memory, learning and executive functioning compared to controls (n=28). In study 2, there was great heterogeneity in the included studies (n=39), with patients of different severities, different methods of diagnosis of TBI, and time of assessment ranging from 1 month to 63 years after TBI. It was possible to find evidence of cognitive, behavioral and self-report changes indicative of increased impulsivity in patients compared to controls. In study 3, patients with mild TBI (n=21) were more impulsive and anxious than controls (n=19) within 30 days after TBI on self-report measures. Mild TBI patients presented higher blood levels of copeptin, GRO, LIGHT/TNFSF14, MMP9 and Lipocalin2/NGAL, and lower levels of MIF, EGF, enolase/NSE and ECA compared to controls. There was an association between impulsivity scores with the markers copeptin, MMP9, Lipocalin-2, LIGHT, APP, NCAM, and with TBI. There was no difference in cognitive measures. The findings point out changes in cognitive functioning in patients with mild TBI in the acute stage (Study 1), and to changes indicative of impulsivity in patients with TBI (studies 2 and 3). In addition, findings regarding the blood markers may indicate changes in central nervous system, related to neuroinflammation, neuronal and vascular damage in mild TBI and its association to impulsivity (study 3). The identification of cognitive-behavioral and neuropsychiatric alterations may contribute to the development of better care and follow-up to patients suffering from mild TBI. Additionally, the better comprehension of mild TBI pathophysiology may open new avenues for the development of novel therapy strategies focus in prevent or minimize mild TBI cognitive and behavioral outcomes.